2015
DOI: 10.3109/02656736.2015.1055832
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of hyperbaric oxygen therapy combined with mild hyperthermia for improving the anti-tumour effects of carboplatin

Abstract: The administration of HBO increased the effects of hyperthermic chemosensitisation to carboplatin at mild temperatures on experimental tumours, particularly when given in the sequence of carboplatin, mild HT, and HBO, a finding that supports previous clinical outcomes for a novel combined therapy using carboplatin plus HT and HBO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
(30 reference statements)
0
14
0
Order By: Relevance
“…Hyperthermia per se is cytotoxic at temperatures >43 C and HBOT exploits the reliance of tumor cells on glycolysis, a major contributor to the upregulation of antioxidant activity responsible for the increased resistance of the tumor to prooxidant chemotherapy and radiation therapies [93]. The synergism between these therapies (ketogenic diet, hyperthermia, HBOT) [23,26,[33][34][35][36] and their effectiveness in increasing the efficacy of conventional therapies have been reported in several studies [26,[35][36][37][38][39][40][41][51][52][53][54]. In NSCLC patients, Ohguri et al administered carboplatin/paclitaxel chemotherapy regimen together with hyperthermia and HBOT; and they reported the protocol as being a feasible and promising modality for treating NSCLC patients [35].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hyperthermia per se is cytotoxic at temperatures >43 C and HBOT exploits the reliance of tumor cells on glycolysis, a major contributor to the upregulation of antioxidant activity responsible for the increased resistance of the tumor to prooxidant chemotherapy and radiation therapies [93]. The synergism between these therapies (ketogenic diet, hyperthermia, HBOT) [23,26,[33][34][35][36] and their effectiveness in increasing the efficacy of conventional therapies have been reported in several studies [26,[35][36][37][38][39][40][41][51][52][53][54]. In NSCLC patients, Ohguri et al administered carboplatin/paclitaxel chemotherapy regimen together with hyperthermia and HBOT; and they reported the protocol as being a feasible and promising modality for treating NSCLC patients [35].…”
Section: Discussionmentioning
confidence: 99%
“…HBOT and hyperthermia was given the same day or the next day sequentially after chemotherapy. Preferentially, hyperthermia was given first, but the two were never given at the same time [35,36]. Patient and survival data were extracted from the records and analyzed.…”
Section: Study Design and Patient Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…HBO treatment overcomes tissue hypoxia and promotes the development of new blood vessels, which are then able to transport drug molecules, thereby rendering the tumour cells more sensitive to chemotherapeutic treatments. Several studies have been conducted to examine the impact of hyperbaric oxygen as an adjuvant agent for use with chemotherapy [ 46 60 ]. Kalns et al [ 47 ] found that the effect of hyperbaric oxygen on the proliferation and sensitivity to chemotherapy of prostate cancer cells in vitro were dependent on the type of cell line.…”
Section: Hyperbaric Oxygen Therapy In Cancer Treatmentmentioning
confidence: 99%